Changing landscape of border higher - Abd Razak, Dzulkifli (2005)
Universities in developed countries are attracting the best brains from the South. We must be aware of this brain drain threat. OVER the past two weeks, there were three international conferences involving highlevel discussions on the subject of crossborder higher education (CBHE) attended by scores of educators, policymakers and heads of institutions and organisations of higher learning all over the world. That these conferences were held so close together and at this time is not a mere coincidence but rather an expression of widespread concern. This is particularly so when framed within the context of borderless or transnational education, the other names for CBHE.